Dansk begrebsordbog: baggrund og metode - Trap-Jensen, Lars (LexicoNordica, 2011)
A Danish thesaurus project is currently underway at the Society for Danish Language and Literature in Copenhagen. Funded by The Carlsberg Foundation, the project runs 2010-2013 with a staff of two full-time editors. It does not start from scratch but draws on already existing lexical data: main input for the thesaurus will be the semantic descriptions of The Danish Dictionary (DDO, 116,000 senses) and the Danish WordNet (DanNet, 65,000 synsets), the latter resource itself built on DDO data. Following an initial analysis of existing thesauri, a macro-structure was adopted close to the one used by Franz Dornseiff: Der deutsche Wortschatz nach Sachgruppen (2004). As a side benefit, this choice makes it easier for the editors to utilize the contents of the only existing thesaurus for Danish, Harry Andersen’s Dansk Begrebsordbog (1945), which itself is no less structurally dependent on the first edition of Dornseiff (1934). One methodological aspect is given particular attention: what should be the main ordering principle within an entry? A final decision has yet to be taken as it is primarily a problem of presentation with no immediate bearing on the editing process, but eventually a conclusion must be reached as the thesaurus is going to appear as a print dictionary, too.